Java message service - Monson-Haefel, Richard (Java series., 2001)
This book is a thorough introduction to Java Message Service (JMS), the standard Java application program interface (API) from Sun Microsystems that supports the formal communication known as "messaging" between computers in a network. JMS provides a common interface to standard messaging protocols and to special messaging services in support of Java programs. The messages exchange crucial data between computers, rather than between users--information such as event notification and service requests. Messaging is often used to coordinate programs in dissimilar systems or written in different pr